Steering the economy : the role of the treasury - Brittan, Samuel (London : Secker & Warburg, 1969)
Part one of this present version is concerned with how economic policy is formed and contains a brief account of the main bodies, international as well as national, that have a role to play in its formation. Part two, the historical section, contains a substantial new chapter on the events following the return of a Labour Government. Part three, analysis and conclusions, draws the threads together. It discusses some controversial questions, including the sterling exchange rate and 'planning'.
Includes index.
Includes bibliographical references: p. 329-334.
ne 21/05/2018
Loans
Keywords: Public Finance